Labour market regulations and efficiency in tourism industry. Issue 4 (June 2023) - Mamatzakis, Emmanuel; Pegkas, Panagiotis; Staikouras, Christos
This study examines the effect of the labour market regulations on Greek tourism industry performance. The tourism industry, the steam engine of the Greek economy, always drives to enhance efforts to reach further savings in operating costs. However, the labour regulations that influence the tourism sector's ability to adjust costs have not been thoroughly investigated. We present a novel methodology that permits the evaluation of the effect of labour market regulations on technical and allocative efficiency in one step. The empirical results demonstrate the complexity of the relationship between labour regulations and efficiency. Labour market liberalization is associated with improvements in allocative efficiency but may have opposite effects on technical efficiency. Policymakers should pay attention to these complicated interactions when planning reforms on labour market. JEL codes : D24, D61, J30, J80, Z30